Visualization of Early Adulthood Overthinking Behavior in Batik Outerwear Clothing - Lidia Vania Sukarno; Retno Purwandari; Budi Hartono (Jurnal Indonesia Sosial Sains, 2026)
Overthinking is a mental health issue that may arise in individuals throughout their lives. Early adulthood is a transitional period from adolescence to adulthood. This period often affects emotional stability and causes anxiety. Excessive anxiety frequently triggers overthinking. The approaches used in this study include developmental psychology theory, the expressionist aesthetic theory, and ergonomic theory. Additionally, the creation process employs the Practice-led Research method, encompassing the stages of preparation, imagination, development of imagination, and execution. The creative process involves the batik lorod (hand-drawn batik) technique with textile dyes using the colet remasol technique. The steps include pattern creation, motif tracing, waxing (canting), dyeing, batik finishing, fabric cutting, sewing, and garment finishing. The final products of this project consist of five outerwear garments, each featuring unique batik colours and designs. These five pieces are titled Fear of the Unknown, Shadows of What-Ifs, Endless Loops, Shattered, and The Sea of Uncertainty. The distinct titles aim to convey the theme of each outerwear